The Effects of foreign aid on government corruption in Sub-Saharan African countries - KWAK, Yunjeong (KDI School, 2015)
Aid effectiveness arises as a key issue in the international development field. Sub-Saharan Africa Countries, in particular, received a huge amount of aid money in the past decades. However, they still remain in a poverty trap due to a lack of good governance. In fact, Dambisa Moyo, a Zambian economist, argues that foreign aid is not effective in Sub-Saharan Africa, as it intensifies government corruption. To examine the effect of aid on government corruption, this paper investigates empirical analysis by using a fixed effect approach with panel data from 40 Sub Saharan countries from 2002 to 2013. This empirical test also shows the effect of not only Net ODA (% of GNI) but also bilateral and multilateral aid (% GNI) on government corruption. The results of the empirical tests show that increasing aid creates more serious corruption, for Net ODA and bilateral and multilateral aid. Even though foreign aid does not improve the quality of governance, it does not mean that we should stop the flow of aid. Rather, clearer and more effective aid monitoring and evaluation are needed on the part of the donors. Recipient governments should also develop mature civic awareness through improved training programs or E-government, which are useful ways to achieve transparency in government.
Thesis(Master) --KDI School:Master of Development Policy,2015